»(Ist fortzusetzen.)« (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
For the late Goethe; questions of continuation; connection; and closure play a central role. It is not without reason that he repeatedly uses the formula »(To be continued).« to mark the incompleteness of his works and to raise the question of the continuity of literary and scientific texts. In ten essays; this volume addresses the question of Goethe’s poetics of continuation; which has so far been neglected in Goethe studies. In addition to the central connection between continuation and the form of the novel for the Wilhelm Meister complex; the volume examines the problem of continuation in the two parts of Faust; before finally considering the question of continuability of works in relation to serial publication and the material conditions of writing. With contributions by Michael Auer | Michael Bies | Sean Franzel | Eva Geulen | Ines Gries | Oliver Grill | Wolfgang Hottner | Anja Lemke | Helmut Müller-Sievers | Cornelia Ortlieb | Cornelia Zumbusch